SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN PADA DESA SAMPIR KECAMATAN WARINGINKURUNG - Waliadi Gunawan; Irma Yunita Ruhiawati; Mochamad Yusuf Romdoni; Mochamad Reza Setiawan (Teknik Informatika Fakultas Ilmu Komputer, 2022)
The population administration system is part of the state administration system, which has avery important role in the government to manage population data. Increasing populationawareness and participation to participate in supporting the development planning of thepopulation administration system to improve services to the public. In line with the objectives ofthe administration of population administration, population registration and civil registrationare an important part of the population administration system that needs to be managed as wellas possible to provide benefits for government improvement and development. Sampler Villageis one of the villages that already use information systems and computers in carrying out dailyactivities. This population information system was built by applying auto control to input errorsthat often occur, besides that it is also equipped with auto control for data that is exchangedwhich causes data redundancy as well as control over information users because it has beenequipped with good user security features so that it is more guaranteed that data will not belost. stolen or lost. Some of these features apply to several important transactions for serviceadministration, including the process of submitting a letter of introduction for a ResidentIdentity Card (KTP), Family Card (KK), birth certificates, and death certificates so that this isexpected to help the process of serving residents and village office tasks become more efficient.faster and more effectively by the expected needs.